Relation between inflammatory cytokine levels in serum and bronchoalveolar lavage fluid and gene polymorphism in young adult patients with bronchiectasis - Ayhan, Gulhan; Tas, Dilaver; Yilmaz, Ismail; Okutan, Oguzhan; Demirer, Ersin; Ayten, Omer; Kartaloglu, Zafer (Journal of Thoracic Disease, 2014)
Aim: Bronchiectasis develops as a result of genetic and environmental factors and its etiopathogenesis is not still clear. Recent studies have revealed that inflammatory cytokines, which are formed as a result of chronic infection and inflammation, play a role in the pathogenesis of bronchiectasis. For this purpose, the level of inflammatory cytokines in bronchiectasis and the presence or absence of a genetic predisposition with the gene polymorphism of these cytokines was investigated. Material and methods: A total of 60 patients, 40 study cases and 20 controls, which were monitored with the diagnosis of bronchiectasis were included in the study. In these individuals, cytokine levels [interleukin (IL)-6, IL-8, IL-10, and tumor necrosis factor (TNF)-α] in serum and bronchoalveolar lavage (BAL) fluid, along with the routine blood tests, were determined. Furthermore, the polymorphism in IL-6, IL-8, IL-10, and TNF-α cytokine genes and its frequency were studied in the obtained DNA by the automatic sequence analysis method and the results were compared. Findings: It was found that in serum and BAL fluid of the patient group, the IL-8 level was high, whereas the IL-10 level was low (P0.05). It was found that in cytokine gene polymorphisms IL-8 -251 A/T, IL-10 -592 A/C, and IL-10 -819 T/C genotypes are associated with increased risk of bronchiectasis. It was detected that the IL-8 -251 A/T genotype increased the risk of having the disease by 4.19 fold. (OR =4.19, 95% CI =1.24-14.17, P=0.021). The IL-10 -592 C/A genotype increased the risk of having the disease by 5.71 fold (OR = 5.71, 95% CI = 1.35-24.06, P=0.017) and the IL-10 -819 T/C genotype increased the risk of having the disease by 5.06 fold (OR =5.06, 95% CI =1.20-21.27, P=0.048). No significant correlation was found between the other polymorphisms and bronchiectasis. Conclusions: The IL-8, IL-10 levels and the gene polymorphism of these cytokines differ. In addition to detecting higher levels of pro-inflammatory IL-8 and lower levels of anti-inflammatory IL-10, detection of gene polymorphism related to these two cytokines in bronchiectasis gives rise to the thought that cytokines may have role in a predisposition to bronchiectasis. However, as the number of patients is small, precise remarks could not be made on this subject. There is need for further studies include a larger number of patients.